RANCANG BANGUN SISTEM BORANG AKREDITASI PROGRAM STUDI TEKNIK ELEKTRO UNIVERSITAS BANGKA BELITUNG - Rudy Kurniawan; Fardhan Arkan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2016)
In this research, a web-based information systems and database applications for charging and preparation Accreditation Forms of the Study Program (Book III-A) in Electrical Engineering Study Program University of Bangka Belitung. The information system accreditation forms of the study program are manufactured with an integrated system with web applications as interactive media and database as data storage media. Web applications and databases can be used as templete to describe the performance of a study program and can be used to document the internal environment to the needs of the process of accreditation. This application contains a accreditation forms of the study program process, which consists of seven existing standards in Accreditation Forms of the Study Program (Book III-A). Given this information system, the charging process Accreditation Forms of the Study Program has been done manually which is so difficult and time consuming can now be done more easily, practical, and everyone can participate in filling the form so that the work in filling out accreditation forms to be faster , This information system also makes it a team of assessors in the assessment of the document because it can be accessed online.